1998
DOI: 10.1038/sj.ijo.0800665
|View full text |Cite
|
Sign up to set email alerts
|

Serum leptin and weight loss in severely obese patients undergoing biliopancreatic diversion

Abstract: OBJECTIVE: To evaluate the in¯uence of body fat and food intake on serum leptin concentration. DESIGN: Longitudinal study of a group of obese patients prior to and at, long term follow-up, after biliopancreatic diversion (BPD), when body weight was steadily reduced and food consumption was similar to or greater than preoperatively. RESULTS: In obese patients, very high serum leptin concentrations were found. Following the operation, with the body weight stable and normalized, a sharp fall of serum leptin conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 5 publications
2
9
1
Order By: Relevance
“…The observations presented in this report further extend information on the effect of anti‐obesity surgery on the above‐mentioned parameters. In some respects, our results are in accordance with earlier findings (20, 21, 22, 23, 24). It is interesting to note that serum glucose concentration and insulin resistance in banded vertical gastroplasty patients reached the values observed in lean patients.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The observations presented in this report further extend information on the effect of anti‐obesity surgery on the above‐mentioned parameters. In some respects, our results are in accordance with earlier findings (20, 21, 22, 23, 24). It is interesting to note that serum glucose concentration and insulin resistance in banded vertical gastroplasty patients reached the values observed in lean patients.…”
Section: Discussionsupporting
confidence: 94%
“…Plasma leptin concentration changes have also been reported in surgically induced weight loss (after gastric bypass operation) (20, 21, 22, 23, 24). Guldstrand et al (20) have suggested that the reduction in insulin concentration is a key factor responsible for serum leptin reduction after vertical banded gastroplasty (20).…”
Section: Introductionmentioning
confidence: 78%
“…In a group of severely obese patients also receiving a biliopancreatic diversion, a normalization of serum leptin concentrations was observed despite food consumption being similar or greater than pre-operatively 16 . In this patient, the decrease in serum leptin concentrations paralleled that of BMI.…”
Section: Discussionmentioning
confidence: 86%
“…This finding is in agreement with previous results obtained in patients with obesity of extreme degree. 21 However, although in severely obese patients serum leptin concentration appears to be strongly associated with eating pattern, the weakly significant positive relationship between leptin and BF mass suggests that adipose tissue still has a Several studies have demonstrated that the tendency to disinhibition and the susceptibility to hunger, as evaluated by the EI, as well as the EDI bulimia score, are higher in BED than in non-BED patients. 22 -24 Furthermore, weight fluctuation due to reducing diet is more frequent in BED patients than in the non-BED individuals.…”
Section: Discussionmentioning
confidence: 99%